Facebook-to-Facebook: online communication and economic cooperation. Issue 11 (25th June 2018) - Abatayo, Anna Lou; Lynham, John; Sherstyuk, Katerina
ABSTRACT: Direct face-to-face communication has traditionally been found to be more effective for fostering economic cooperation than any form of indirect, mediated communication. We inquire whether this is still the case since most young adults routinely use texting and online social media to communicate with each other. We find that young adults in our laboratory public goods experiment are just as adept at finding and sustaining cooperative agreements when communicating within a Facebook group and through online chat as they are in person.